Determining the legal age for marriage: a comparative study of Islamic jurisprudence and contemporary legal frameworks - Chui, Khadija; Abdulrahman, Manswab Mahsen; Mohamed, Hossam El-Din Ibrahim (International Scientific Research Academy (isrAcademy), Turkiye, 2025)
This paper examines the determination of the legal age for marriage through a comparative study of Islamic jurisprudence and contemporary legal frameworks. Grounded in classical Islamic legal principles, the research investigates the rulings of the four major Sunni schools of thought—Hanafi, Maliki, Shafi'i, and Hanbali—on the age of marriage, emphasizing the concepts of physical and mental maturity (bulugh and rushd). It contrasts these Islamic perspectives with modern legal standards, particularly those established in international human rights instruments and the national laws of Muslim-majority countries. The study highlights the diversity of interpretations within Islamic jurisprudence, ranging from flexible rulings influenced by cultural contexts to fixed legal standards imposed by modern states. It also discusses the legal, social, and ethical implications of early marriage, especially for women and children, addressing contemporary challenges such as gender equality, child protection, and individual rights. Employing a qualitative and analytical approach, this research combines traditional Islamic jurisprudential (fiqh) methodologies with contemporary legal and ethical analysis. The study finds that Muslim jurists differ on the permissibility of minor marriages. It concludes by offering practical recommendations for Muslim scholars and legal experts to promote gender equality, protect minors, and prevent harmful practices such as child marriage.